2018
DOI: 10.13075/ijomeh.1896.01256
|View full text |Cite
|
Sign up to set email alerts
|

The mediating role of nurses’ professional commitment in the relationship between core self-evaluation and job satisfaction

Abstract: Nurses who are more committed to their work, regardless of the structure of personality, have greater satisfaction in their work. Int J Occup Med Environ Health 2018;31(5):649-658.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 35 publications
(42 reference statements)
5
23
0
2
Order By: Relevance
“…This is inseparable from the results of previous tests which are known that organizational culture directly influences professional commitment and professional commitment directly influences innovative behavior. These results support previous findings which indicated professional commitment as a mediator variable (Barać et al, 2018;Nikpour, 2018;Sari & Seniati, 2019). Thus to maximize the influence of organizational culture on flight instructors innovative behavior requires the support from professional commitment factors.…”
Section: Discussion:-supporting
confidence: 90%
“…This is inseparable from the results of previous tests which are known that organizational culture directly influences professional commitment and professional commitment directly influences innovative behavior. These results support previous findings which indicated professional commitment as a mediator variable (Barać et al, 2018;Nikpour, 2018;Sari & Seniati, 2019). Thus to maximize the influence of organizational culture on flight instructors innovative behavior requires the support from professional commitment factors.…”
Section: Discussion:-supporting
confidence: 90%
“…In one of these studies, Moradi et al (2013) found a .324 (weak) correlation between job satisfaction and occupational commitment. In another study, Barac et al (2018) found a .464 (moderate) correlation between job satisfaction and occupational commitment. The results revealed in the above-mentioned studies suggest that there may be factors affecting the relationship between job satisfaction and occupational commitment.…”
Section: Perception Of Private Security Police Cooperationmentioning
confidence: 87%
“…The results revealed in the above-mentioned studies suggest that there may be factors affecting the relationship between job satisfaction and occupational commitment. As a matter of fact, Barac et al (2018) found that core self-evaluation partially mediated the relationship between professional commitment and job satisfaction. The existence of the partial mediating effect indicates that another variable can mediate the relationship between the dependent and the independent variable (Baron and Kenny, 1986: 116).…”
Section: Perception Of Private Security Police Cooperationmentioning
confidence: 99%
See 2 more Smart Citations